eCM 2014
DOI: 10.22203/ecm.v027a13
|View full text |Cite
|
Sign up to set email alerts
|

Constitutive and inducible co-expression systems for non-viral osteoinductive gene therapy

Abstract: Tissue regenerative gene therapy requires expression strategies that deliver therapeutic effective amounts of transgenes. As physiological expression patterns are more complex than high-level expression of a singular therapeutic gene, we aimed at constitutive or inducible co-expression of 2 transgenes simultaneously.Co-expression of human bone morphogenetic protein 2 and 7 (BMP2/7) from constitutively expressing and doxycycline inducible plasmids was evaluated in vitro in C2C12 cells with osteocalcin reporter … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
13
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 76 publications
3
13
0
Order By: Relevance
“…Preparation and in vitro testing of the BMP2 and BMP7 plasmids are described elsewhere [23]. The plasmids were amplified in E.coli TOP10 (Life Technologies Ltd, Paisely, UK, ♯C404003) and isolated as endotoxin-free maxipreps using the EndoFree Plasmid Maxi or Giga kits (Quiagen GmbH, Hilden, Germany, ♯12362).…”
Section: Bmp2 and Bmp7 Plasmidsmentioning
confidence: 99%
“…Preparation and in vitro testing of the BMP2 and BMP7 plasmids are described elsewhere [23]. The plasmids were amplified in E.coli TOP10 (Life Technologies Ltd, Paisely, UK, ♯C404003) and isolated as endotoxin-free maxipreps using the EndoFree Plasmid Maxi or Giga kits (Quiagen GmbH, Hilden, Germany, ♯12362).…”
Section: Bmp2 and Bmp7 Plasmidsmentioning
confidence: 99%
“…They can exist as homodimers, where both sub-units are identical, such as BMP-2, and also as heterodimers, where the sub-units are different, for example BMP-2/4 and BMP-2/7. While both types are active, some studies have demonstrated that heterodimers such as BMP-2/4 and BMP-2/7 are more active than homodimers [18][19][20]. For this reason, we sought to investigate the use of a multi-cistronic plasmid encoding BMP-2 and BMP-7 ( Figure 1B) which may induce expression of BMP-2/7 heterodimers and enhance the efficiency of the geneactivated scaffold [20].…”
mentioning
confidence: 99%
“…The data essentially demonstrate that it is possible to control gene transfer‐dependent osteogenic differentiation within GAMs in vitro using an external stimulus. The data obtained with the TetON system also suggest that additional control of transgene expression and subsequent osteogenic differentiation can be incorporated into the novel GAM by judiciously manipulating control of expression of therapeutic nucleic acid constructs that would respond to inducers in vivo at a molecular genetic level as shown in previous work (Feichtinger et al ., ).…”
Section: Discussionmentioning
confidence: 97%